PIK3CA mutation in non-metastatic triple-negative breast cancer as a potential biomarker of early relapse: A case report - Valencia, GA (2021)
Background: Currently, the detection of PIK3CA mutations is of special interest in personalized medicine because it is frequently found in triple-negative breast cancer (TNBC). The PI3KCA mutation is an independent negative prognostic factor for survival in metastatic breast cancer, and its prognostic value in liquid biopsy as a biomarker of treatment and early relapse is under investigation, both for metastatic disease and neoadjuvant scenario with curative intent. Case summary: A 54-year-old female patient with TNBC clinical stage IIIA, who, after receiving neoadjuvant chemotherapy (based on anthracyclines and taxanes), surgery, radiotherapy, and adjuvant capecitabine, was detected with a PI3KCA mutation in tissue and peripheral blood (ctDNA in liquid biopsy). After 10 mo, the patient had disease relapse of left cervical node disease. Conclusion: The detection of PIK3CA mutation in TNBC after neoadjuvant treatment might be associated with early relapse or rapid disease progression.